Psychopathology of Work-Family and Family-Work Conflicts among Dual Income Earners: An Empirical Analysis from Cosmopolitan Lagos - Akinbode, Gabriel A.; Folusho, AYODEJI; Uzochukwu, ISRAEL Nwachinemere (Advances in Social Sciences Research Journal, 2018)
The study examined the psychopathological consequences of work-family and family-work conflict among dual income earner workers in Lagos metropolis. Employee’s perceptions as reflected in self reports constituted the central features of a model underlying the study, as they were believed to be related to the individual experience. A total sample comprising 626 dual-income earners employees comprises of 363 males and 263 females were drawn from human service private and public organization. Precisely, 348 of these workers were drawn from private sector and while 278 were drawn from public sector organizations respectively. The study was anchored on the Role-Strain Theory (Greenhaus & Beutell 1985) and Job-Demand-Control model (Karasek, 1979) .It was hypothesized that (i) there will be a significant relationship between family-work conflict, work-family conflict workers emotionality, psycho-physiological stress symptoms and affectivity among private and public sector worker in Lagos. Results of analyses conducted revealed that: (i) emotional exhaustion, emotional effort, physical and psychological stress symptoms had significant positive correlations with family-work and work-family conflict. (ii) positive affect had a negative significant correlations with family-to-work conflict and work-to-family conflict. (iii) reported psychopathological symptoms (i.e. emotionality, negative affect and psycho-physiological stress symptoms) were higher among private sector workers compared to public sector counterparts. Based on the findings recommendations were made one of which is that government sector as well as private organizations should make provision for flex time or on-site child care centres that would help to provide resources supporting family care or flexibility in the timing of work to enable women’s participation in both work and family roles. Implications for the research and the bidirectional influences of work and family are discussed.